2021
DOI: 10.1097/qai.0000000000002794
|View full text |Cite
|
Sign up to set email alerts
|

Predicting, Diagnosing, and Treating Acute and Early HIV Infection in a Public Sector Facility in Eswatini

Abstract: Background:The lack of acute and early HIV infection (AEHI) diagnosis and care contributes to high HIV incidence in resourcelimited settings. We aimed to assess the yield of AEHI, predict and diagnose AEHI, and describe AEHI care outcomes in a public sector setting in Eswatini.Setting: This study was conducted in Nhlangano outpatient department from March 2019 to March 2020.Methods: Adults at risk of AEHI underwent diagnostic testing for AEHI with the quantitative Xpert HIV-1 viral load (VL) assay. AEHI was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…Nevertheless, the low sensitivity of the HIV antigen-detection component of the 4 th -generation Alere TM HIV Combo RDT was further confirmed in the testing of three commercial HIV-1 seroconversion panels. Other studies evaluating the 4 th -generation Alere TM HIV Combo RDT have reported sensitivities ranging from around 0.94% to 95% in the detection of HIV acute infections [11,22,24,[39][40][41][42][43][44].…”
Section: Discussionmentioning
confidence: 98%
“…Nevertheless, the low sensitivity of the HIV antigen-detection component of the 4 th -generation Alere TM HIV Combo RDT was further confirmed in the testing of three commercial HIV-1 seroconversion panels. Other studies evaluating the 4 th -generation Alere TM HIV Combo RDT have reported sensitivities ranging from around 0.94% to 95% in the detection of HIV acute infections [11,22,24,[39][40][41][42][43][44].…”
Section: Discussionmentioning
confidence: 98%
“…In addition, a 2021 study conducted in Eswatini evaluating the use of a predictors risk score and viral load testing to identify acute and early HIV concluded that such an approach to diagnosis and care seems possible in resource-limited settings. 48 Their findings suggest that the TMP intervention is potentially feasible and impactful. Missing HIV diagnoses when patients are most infectious is no longer acceptable if we truly wish to end the HIV epidemic.…”
Section: Discussionmentioning
confidence: 99%
“…To realize the public health benefits of identifying and treating persons with AHI, early ART must effectively and efficiently reduce blood and genital tract VLs. Rapid reduction of blood VLs after ART initiation during AHI have been reported among men and women in Eswatini (median days to <40 copies/mL: 56), 7 South African women (median days to <20 copies/mL: 16), 6 and Thai men who have sex with men (MSM) (median days to <50 copies/mL: 82). 16 In the United States, the median time to viral suppression (<200 copies/mL) was 131 days after AHI diagnosis, largely reflecting delays in linkage to care.…”
Section: Discussionmentioning
confidence: 99%
“…been reported among men and women in Eswatini (median days to ,40 copies/mL: 56), 7 South African women (median days to ,20 copies/mL: 16), 6 and Thai men who have sex with men (MSM) (median days to ,50 copies/mL: 82). 16 In the United States, the median time to viral suppression (,200 copies/mL) was 131 days after AHI diagnosis, largely reflecting delays in linkage to care.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation